The South African Police Services: towards a model of empowerment - Eugene van Niekerk; Annette Prins (Acta Academica)
Police officers currently suffer unacceptable levels of physical and psychological trauma. This has an impact on their personal and job satisfaction and can negatively affect their ability to render effective service to the community. A four-phase model of primary intervention, intended to orchestrate intervention strategies in order to meet the demands on mental health in the SAPS is proposed in this study. It is argued that the four-phase model proposed here can have a significant positive effect on the overall effectiveness of mental health intervention within the SAPS, increasing levels of personal adjustment and enhancing organisational functionality. This should contribute to the achievement of more acceptable levels of synergy between the SAPS and the various South African communities it serves: in short, towards empowerment for all concerned.